Simultaneous Regulation of Coordination Environment and Electrode Interface for Highly Stable Zinc Anode Using a Bifunctional Citrulline Additive - Chen, Jingzhu; Liu, Ning; Dong, Wujie; Xu, Yang; Cao, Yuge; Zhang, Shicong; Hou, Jingshan; Bi, Hui; Lin, Tianquan; Huang, Fu‐Qiang (Advanced functional materials, 2024)
Aqueous zinc ion batteries are promising candidates for large‐scale energy storage. Nonetheless, the stability of Zn anodes in aqueous electrolytes is compromised by dendritic growth and undesirable side reactions. In this article, citrulline (Cit), a biocompatible compound, is investigated as an electrolyte additive to achieve superior stability of Zn anodes. Experimental results and theoretical calculations demonstrate that the Cit, serving as a bifunctional additive, possesses abundant highly polar groups (─NH2 and ─COOH) that facilitate strong interactions with Zn2+ and Zn metal. This dual regulation of the Zn2+ solvation shell and the electrical double layer at the anode/electrolyte interface effectively mitigates dendrite growth and suppresses interface side reactions, resulting in exceptional stability of Zn anode. Consequently, Zn||Zn symmetric batteries incorporating the Cit additive exhibit stable operation for over 1600 h at 1.0 mA cm−2 and 1.0 mAh cm−2, and maintain stable cycling for 650 h even under demanding conditions of 10.0 mA cm−2 and 10.0 mAh cm−2, corresponding to an ultra‐high cumulative plated capacity of 3.25 Ah cm−2. Furthermore, Zn||Cu asymmetric batteries achieve a remarkable Coulombic efficiency of 99.6% at 1.0 mA cm−2 and 0.5 mAh cm−2. These advancements also extend to the improved performance of assembled full batteries. Ultra‐high stability and ultra‐long cycle aqueous zinc ion batteries are achieved by citrulline introduction. The citrulline can replace one water molecule from the solvation shell to improve the deposition kinetics of Zn2+. The citrulline can adsorb on the Zn anode surface to block water molecules and regulate the deposition behavior of Zn2+.